Tolerance of rice cultivars to salinity - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 1991)
Salinity is a serious growth-limiting factor for rice production in arid and semi-arid regions of the world. Data related to the reaction of rice cultivars to salinity are limited, especially for large numbers of cultivars. Forty rice cultivars were grown in a greenhouse in soil adjusted to different levels of salinity by applying 0.34 mol 1-1 of NaCl solution. The resulting salinity levels were: 0.39 (control), 5, and 10 dS m-1 saturation extract conductivity. Significant varietal differences were found in relation to salinity tolerance. Based on relative dry matter yield of shoots at growth depressing salinity levels, rice cultivars were classified as tolerant, moderately tolerant, or moderately susceptible, and suscep-tible. The effect of salinity on concentrations and uptake of nutrients was observed. The sensitive and tolerant cultivars/lines identified may be beneficial in future breeding and phy-siological studies.